Impact of Side Effects on Adherence in Drug-Resistance Tuberculosis Treatment at RSD dr. Soebandi Jember - Machlaurin, Afifah; Poerwahyuningrum, Neny; Fajrin, Fifteen Aprilla; Rahardjo, Angga Mardro; Prasetyowati, Irma; Arwi, Khoiriyatul Muhlishoh (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Tuberculosis (TB) is the leading cause of death from infectious disease worldwide. Patient adherence to treatment is crucial for therapy which side effects of tuberculosis treatment are a significant factor affecting compliance. This study aims to analyze the impact of side effects from anti-tuberculosis drugs on the medication adherence of Drug Resistant Tuberculosis patients (DR-TB) at RSD dr. Soebandi in Jember. This study was a retrospective cohort observational that included 245 DR-TB patients register at the dr. Soebandi Hospital from January 2021-December 2023. The electronic medical records, web-based tuberculosis information systems (SITB), and data filling sheets was used. The Proportion of Days Covered (PDC) method was used to evaluate the medication adherence. Data analysis was conducted in SPSS 27.0. Ten patients were excluded due to HIV comorbidities, resulting a final sample of 235 patients. The findings revealed that 53.6% of patients were non-adherence. The three most common types of side effects were gastrointestinal (43.4%), musculoskeletal (29.8%) and skin-related side effects (16.6%). The multivariate logistic regression showed that adherence was significantly reduced by the presence of side effects (aOR: 0,153; 95%CI 0,052-0,448), the number of side effects >2 types (aOR: 0,290; 95%CI 0,101-0,837), and the musculoskeletal-related side effects (aOR: 0,441; 95%CI 0,201-0,972).